Retinal microvasculature and white matter microstructure: The Rotterdam Study. (6th September 2016) - Mutlu, Unal; Cremers, Lotte G.M.; de Groot, Marius; Hofman, Albert; Niessen, Wiro J.; van der Lugt, Aad; Klaver, Caroline C.W.; Ikram, M. Arfan; Vernooij, Meike W.; Ikram, M. Kamran
Abstract : Objective: To investigate whether retinal microvascular damage is related to normal-appearing white matter microstructure on diffusion tensor MRI. Methods: We included 2, 436 participants (age ≥45 years) from the population-based Rotterdam Study (2005–2009) who had gradable retinal images and brain MRI scans. Retinal arteriolar and venular calibers were measured semiautomatically on fundus photographs. White matter microstructure was assessed using diffusion tensor MRI. We used linear regression models to investigate the associations of retinal vascular calibers with markers of normal-appearing white matter microstructure, adjusting for age, sex, the fellow vascular caliber, and additionally for structural MRI markers and cardiovascular risk factors. Results: Narrower arterioles and wider venules were associated with poor white matter microstructure: adjusted difference in fractional anisotropy per SD decrease in arteriolar caliber −0.061 (95% confidence interval −0.106 to −0.016), increase in venular caliber −0.054 (−0.096 to −0.011), adjusted difference in mean diffusivity per SD decrease in arteriolar caliber 0.048 (0.007–0.088), and increase in venular caliber 0.047 (0.008–0.085). The associations for venules were more prominent in women. Conclusions: Retinal vascular calibers are related to normal-appearing white matter microstructure. This suggests that microvascular damage in the white matter is more widespread than visually detectable as white matter lesions.